Vascular malformation of the parotid gland: a rare case report - Bhatia, Chisel; Dalal, Satish; Sattibabu, Vundavalli; Beniwal, Jagat P. (International Surgery Journal, 2017)
Vascular malformation of the parotid gland is an extremely rare condition with very few reported cases in the literature. Here we report a case of a 55 years old, female who presented with the complaint of swelling in the right parotid region for one year. Imaging revealed a vascular malformation involving the superficial lobe of the right parotid gland. Superficial Parotidectomy was done and histopathology was consistent with the diagnosis of vascular malformation of the parotid.